Krimighna Approach in the Management of Scalp Psoriasis – A Twin Case Report - Savalagimath, Mahesh P; Pol, Neha K; Ajith , Krishnan M; Jiragale, Pooja Gurupad (International Research Journal of Ayurveda & Yoga, 2022)
Psoriasis is a chronic, debilitating disease that commonly involves the scalp. Despite a wide range of therapy options, scalp psoriasis remains challenging to treat, highlighting a long-standing unmet need for the safe and effective treatments. Many topical therapies for scalp psoriasis are also difficult or unpleasant to apply, resulting in decreased adherence and efficacy. In brief, the high level of patient dissatisfaction with currently available treatments for psoriasis supports the need for new, effective and well-tolerated treatment options for scalp psoriasis. Two cases of Scalp Psoriasis approached our outpatient department of dermatology complaining of whitish gray skin lesions over scalp with mild itching. The medical, social, and family history was insignificant. As the treatment protocols available for scalp psoriasis in modern science includes only such as topical corticosteroids, topical vitamin D analogues, topical tar-based preparations, topical salicylic acid, etc., a full cure for scalp psoriasis is difficult due to the condition’s recurrent nature. Hence, a treatment protocol is necessary to accelerate the healing process, preventing its spread and recurrence and for cosmetic reasons. When it comes to Psoriasis, irrespective of type of psoriasis, the main cause is disturbed Immunity or Autoimmunity which can be related with the term “Krimighnatva” of the body in Ayurveda. Hence the present twin case reports of scalp psoriasis which has shown encouraging results serves as an example in providing the role of Krimighna Chikitsa in management of scalp psoriasis.